Long term results of open complex abdominal wall hernia repair with self-gripping mesh: A retrospective cohort study. (August 2017) - Kroese, Leonard F.; van Eeghem, Lien H.A.; Verhelst, Joost; Jeekel, Johannes; Kleinrensink, Gert-Jan; Lange, Johan F.
Abstract: Background: In case of complex ventral hernias, Rives-Stoppa and component separation technique are considered as favourable treatment techniques. However, mesh-related complications like recurrence, infection and chronic pain are still a common problem after mesh repair. Previous studies have reported promising results of the use of a self-gripping mesh (ProGrip™) in incisional hernia repair. This study aimed to evaluate the long term results of this mesh for complex ventral hernia treatment. Materials and methods: Patients with complex ventral hernia undergoing repair between June 2012 and June 2015, using the ProGrip™-mesh in retromuscular position, were included. All patients visited the outpatient clinic to evaluate short term complications and recurrence. After at least one year, telephone interviews were conducted to evaluate long term results. Results: A total of 46 patients (median age 59 years) were included. 40 patients (87%) were diagnosed with incisional hernia. Seven patients (18%) had incisional hernia combined with another hernia. Four patients (8.7%) had an umbilical hernia, one patient (2.2%) had an epigastric hernia and one patient (2.2%) had rectus diastasis. 39 patients completed follow-up. Median follow-up was 25 months (IQR: 19–35 months). 28 patients (72%) did not report any complaints. Nine patients reported pain (average VAS of 1.7). Two patients developed a recurrence requiring reoperation. One patient developed mesh infection requiring reoperation. Conclusion: Long term results of the use of a self-gripping mesh for complex abdominal wall hernias show a low recurrence rate, even in complex hernia cases. This makes the mesh a good choice in this difficult patient group. Highlights: A self-gripping mesh is feasible to place in retromuscular position without sutures. Long-term results of the use of a self-gripping mesh seem promising. Prospective registries should provide more insights on results after longer periods of follow-up.